Non-classical properties of photon-added-and-subtracted two-mode pair coherent state - Hồ, Sỹ Chương; Hồ, Ngọc Trung; Trương, Minh Đức (Hue University Journal of Science: Natural Science, 2022)
In this paper, we study the non-classical properties such as two-mode sum squeezing, two-mode difference squeezing, and higher-order two-mode antibunching properties of the photon-added-and-subtracted two-mode pair coherent state (PAASTMPCS). The results in the squeezing property show that the PAASTMPCS has two-mode sum squeezing but no two-mode difference squeezing. The two-mode sum squeezing of the PAASTMPCS always appears when adding and subtracting photons to two modes of a pair coherent state (PCS). Furthermore, the PAASTMPCS has higher-order two-mode antibunching in any order, and this property is enhanced when photons are simultaneously added and subtracted to two modes of the PCS. Thereby, the role of the photon addition and the photon subtraction has been confirmed by enhancing the non-classical properties of the PAASTMPCS.